Penentuan Status Tagihan Pelanggan Menggunakan Fuzzy C-Means Pada Aplikasi Weberp - Rakhmat Arianto; Nur Haryadi (KILAT, 2016)
On the sale of goods and services cctv21.com before the release of a bill to consumers, so the staff concerned sales order (sales order) prior to the consumer and then after all the desired items appropriate then further processed and made sales order invoice (invoice) name contains the description, quantity and price paid. Problems arise when there are some consumers who do not pay bills or forget to pay the bill for the services of installation of CCTV and the like. for payment deadlines in the system that is running a list of charges grouped into 30 days, 90 days, 180 days, 210 days to 360 days. Fuzzy clustering is a technique to determine the optimal cluster in a vector space based on the normal form for the Euclidean distance between vectors. Fuzzy clustering is very useful for modeling fuzzy, especially in identifying fuzzy rules. In cctv21.com companies already using the previous ERP for billing invoice to the customer can be seen from the menu customer aged balance / overdues report. Then from the system menu of existing companies want to add features to the ERP which this feature can determine the level of interest of consumer bills to be somewhat (slightly) urgent, urgent or very urgent.